Sacral neuromodulation for faecal incontinence – 10 years' experience at a Scottish tertiary centre. Issue 4 (August 2018) - Koh, Hoey; McSorley, Stephen; Hunt, Sarah; Quinn, Martha; MacKay, Graham; Anderson, John
Abstract: Introduction: Sacral nerve stimulation (SNS) is increasingly popular in the management of faecal incontinence. This paper reports the first 10-year experience of SNS in the management of faecal incontinence at a tertiary referral centre. Data was collected in a prospectively maintained database. Results: In total 130 patients were referred. The majority were women (94%) under 75-year-old (98%). Seven patients were found to have full-thickness rectal prolapse at the initial work-up and proceeded to rectopexy. Eighty-three patients underwent temporary SNS testing with 73.5% positive outcome, of which 52 patients had permanent implant insertion. There were four failures of SNS (7%) following implantation despite successful temporary testing, seven infection, one lead migration and three post-operative pain/numbness. One patient subsequently developed colorectal cancer requiring SNS removal. A higher frequency of episodes of incontinence was associated with positive SNS outcome (p = 0.007). There was no significant association between age, sex, type of faecal incontinence, previous anorectal/pelvic surgery, colonoscopic or USS findings and the likelihood of successful SNS. Of the 52 patients with SNS implants, 27 patients were seen only once for follow-up; the remaining 25 patients were seen more than once – five of these were part of our initial cases of routine 6- and 12-monthly follow-up, 6 patients were seen for adjustment of voltages, whereas the remaining 14 patients were seen for complications of the implants. If the initial five patients were excluded, only 38% of patients would have been seen more frequently on an as-required basis. Conclusion: SNS is a safe and effective option in the management of faecal incontinence. Of the initial work-up, endoscopy and examination-under-anaesthesia (EUA) or proctogram are essential and more likely to influence the likelihood of suitability of SNS testing. A patient-led drop-in approach to follow-up is feasible to allow patients to be seen on an as-required basis.